Public Perception Against Women Education in Central Kalimantan province Katingan - Desi Erawati (STAI Miftahul Ula Nganjuk, 2018)
Women in the different spheres of both educational, religious, social, cultural and even economy became the center of special attention from various circles. This study is more focus on how the public perception of women's education and the factors that influence the public perception of women's education in the province of Central Kalimantan. Results show there is three classifications field public perception. The first group says that women must have high academic spirit in order to quality education d family, while the second shows that may be educated but also vice versa depending on the economic conditions were the pretty situation. The latter suggests that women do not need to be well educated because it focused on domestic work.